Long-term exposure to traffic-related air pollution and temperature increases gynecological cancers. (15th February 2023) - Liao, Hongsen; Murithi, Rachael Gakii; Lu, Chan; Yang, Wenhui; Liu, Zijing; Cao, Lanqin
Abstract: Background: Cervical, endometrial, and ovarian cancers are three major gynecological cancers (GCs) leading to heavy disease burden and high mortality among women worldwide, which are associated with environmental exposure. However, the role of air pollution and temperature on GCs remains unclear. Objective: To assess the combined effects of short-term, medium-term, and long-term exposure to ambient air pollution and temperature indicators on GCs in women. Methods: A case-control study was conducted in XiangYa Hospital from 2010 to 2018 at Changsha, China. A standard questionnaire was designed to collect the health status and personal factors of 305 cases with GCs including cervical, endometrial, and ovarian cancers and 399 healthy women as control group. Personal exposure to ambient air pollution (PM10, SO2, and NO2 ), temperature, and diurnal temperature variation (DTV) during past one year, past five years, and past ten years was calculated by inverse distance weighted (IDW) method based on each subject's home address. Multiple logistic regression model was used to analyse the relationship of GCs with outdoor air pollution and temperature indicators. Results: Exposure to NO2 during past five years and past ten years was significantly associated with GCs, with adjusted ORs (95% CI) of 1.40 (1.02–1.91) and 1.41 (1.03–1.93). Furthermore, an increase in temperature during past ten years was related with GCs, with OR (95% CI) = 1.95 (1.16–3.25). We strikingly found that high temperature increased the effect of long-term exposure to PM10 and NO2 during past ten years on GCs, while low DTV elevated GCs risk of air pollution exposure. Sensitivity analysis suggests that some specific subjects were more susceptible to the effect of air pollution and temperature indicators on GCs. Conclusion: Relatively long-term exposure to traffic-related air pollution (NO2 ) and increased temperature played important roles in the development of women's GCs. There may be interactions between air pollution and temperature indicators on GCs. Graphical abstract: Image 1 Highlights: Exposure to NO2 longer than 5 and 10 years was associated with gynecological cancers (GCs). Long-term exposure to an increase in temperature elevated GC risk. High temperature significantly increased effect of long-term exposure to NO2 on GCs. Low diurnal temperature variation elevated GT risk of PM10 and/or NO2 exposure. There are interactions of traffic-related air pollution and temperature indicators on risk of GCs.